MULTI LEVEL GOVERNMENT COLLABORATION IN INDONESIA CASE STUDY OF BORDER MANAGEMENT AGENCY IN WEST KALIMANTAN - KARTIKA, AYU PRISSA ([Yogyakarta] : Universitas Gadjah Mada, 2015)
Border area problems are very complex because they are under the authority of the central government in terms of state sovereignty, defense and security, as well as foreign relations, but it is the local governments that have the authority to manage the border area in the framework of regional autonomy. This study examines the management of the border area by the national, West Kalimantan province and regency level authorities to conduct a broader perspective about the effectiveness of multi-level government collaboration in border management at West Kalimantan. This research is using case study method through explanatory activities and the results are presented in the form of descriptive narrative. The research using every evidence as a holistic approach and the analysis is carried out by describing the relationships among three levels of the agency and how they operate in the domain of border management. The reason of using this method in this research because the researcher has limited time and chances to involve with the process of management, by using case study is the ability of this method to connected with all of sources, document, and interview. The results of our study show that the National Border Management Agency as the highest level of border management agency still have many obstacles in its institution itself. The National Border Management Agency was expected to be an agency with multi-authority, but in fact it only has a role as a coordination agency. This affects the management at the levels below, because they must wait for the slow and doubtful response from the central level. This is a problem especially in case of West Kalimantan, which had a pilot project of border management in Indonesia five years before the National Border Management Agency was established.